PENGGUNAAN BIG BOOK DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI PADA KELOMPOK B DI RA BAITUL MU’MININ DESA GUNUNGREJO KECAMATAN SINGOSARI KABUPATEN MALANG - Siti Maisaroh; Rosichin Mansur; Ika Anggraheni (UNISMA, 2021)
The language ability of RA Baitul Mu'minin's children is low. This is one of the reasons for learning media that is less varied. The selection of the right media will greatly affect the learning outcomes obtained. Listening, speaking, reading, and writing skills are four aspects that must be mastered by children to continue higher education. For this reason, Classroom Action Research was carried out with the selection of Big Book media. The objectives of this study are: 1) To determine the process of using Big Book media, and; 2) To find out the impact of using Big Book media in an effort to improve children's language skills. The research subjects were 19 children. Data collection techniques using observation and documentation. The data analysis technique was carried out with quantitative and qualitative descriptive. The criteria for the success of this study are when the child's language skills increase and get an average percentage of more than 80%.. The results of this study indicate an increase in language skills where the initial observation was only 49.01%. However, after using Big Book in the first cycle, the success rate achieved was 71.2%. Therefore, repeated research was carried out so that in the second cycle there was an increase of 87.2%. Based on this research, it can be concluded that the use of Big Book media can improve the language skills of early childhood in group B at RA Baitul Mu'minin Gunungrejo Singosari Malang.